Sapindus mukorossi seed shell extract mediated green synthesis of CuO nanostructures: an efficient catalyst for C–N bond-forming reactions. Issue 2 (8th December 2021) - Saikia, Tulan Chandra; Iraqui, Saddam; Khan, Aslam; Rashid, Md. Harunar
Abstract : An effective biogenic approach is proposed to synthesize size-tunable CuO nanostructures using seed shell extract of Sapindus mukorossi plant to use as efficient catalysts for conjugate addition of amines to acrylonitrile under ambient conditions. Abstract : Catalytic reactions have been used for the synthesis of vital structures containing a C–N bond. The C–N bond-forming reaction is regarded as one of the most popular and efficient methods for the synthesis of many bioactive molecules. The design and application of environmentally friendly catalysts to reduce the amount of toxic waste is essential for such C–N bond-formation reactions. Herein, an effective biogenic approach is reported for the synthesis of size-tunable CuO nanostructures for use as catalysts in C–N bond-formation reactions. The synthesis has been carried out via a hydrothermal method in the presence of the seed shell extract of the Sapindus mukorossi plant followed by calcination in air. An X-ray diffraction (XRD) study reveals that the synthesized CuO nanostructures are crystalline and are free from any impurities. An electron microscopy study reveals that the shape of the CuO nanostructures is more or less homogeneous and that the phytochemicals present in the shell extract perform a key role in controlling the size of the formed CuO nanostructures. These newly developed CuO nanostructures can be used as efficient catalysts for the conjugate addition of amines to acrylonitrile with excellent yields under mild reaction conditions. The protocol is simple and applies to different substituted aryl and alkylamines. The catalyst system is more effective than other supported catalysts and needs no acid, base or ligand to promote the reaction. The catalyst is stable and is reusable up to five cycles with minimal loss of catalytic activity.